An Anthology of British Neo-Latin Literature - Manuwald, Gesine (Bloomsbury Neo-Latin Series: Early Modern Texts and Anthologies Ser, 2020)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- List of Illustrations -- List of Contributors -- Preface -- Introduction -- Neo-Latin as a literary medium -- British Neo-Latin literature -- Overview of Neo-Latin literary genres -- Aims and coverage of this volume -- Latin texts: sources and conventions -- Further reading -- 1 Utopia: Elsewhere and Nowhere Thomas More (1478-1535), Extracts from Utopia -- Introduction -- Bibliography -- Source of the Latin text -- Latin text -- English translation -- Commentary -- 2 An Early Tudor Antiquarian at Bath John Leland (c. 1503-1552), De thermis Britannicis -- Introduction -- Notes -- Bibliography -- Source of the Latin text -- Latin text -- English translation -- Commentary -- 3 The Nature of the Universe George Buchanan (1506-1582), De sphaera 1.1-51 -- Introduction -- Bibliography -- Source of the Latin text -- Latin text -- English translation -- Commentary -- 4 A Celebration of Queen Elizabeth I's Coronation in Verse Walter Haddon (1515-1572), In . . . Elisabethae regimen -- Introduction -- Bibliography -- Source of the Latin text -- Latin text -- English translation -- Commentary -- 5 The Latin University Orations of Queen Elizabeth I Queen Elizabeth I (1533-1603), Speeches of 1566 and 1592 -- Introduction -- Bibliography -- Sources of the Latin text and the English translation -- Latin text -- English translation -- Commentary -- 6 Female Funerary Verse Elizabeth Cooke Hoby Russell (1540-1609), Epitaphic Poems -- Introduction -- Bibliography -- Source of the Latin text -- Latin Text -- English translation -- Commentary -- 7 On Writing about Britain William Camden (1551-1623), Prefatory Letter to Britannia -- Introduction -- Bibliography -- Source of the Latin text -- Latin text -- Modern English translation -- Commentary.